Transitioning towards zero waste in the agri-food supply chain: a review of sustainable circular agri-food supply chain - Alif Andika; Tomy Perdana; Diah Chaerani; Dhanan Sarwo Utomo (Sustainable Futures)
This paper reviews multiple aspects of sustainability and the crucial involvement of stakeholders in promoting Circular Agri-Food Supply Chains by employing bibliometric analysis using Bibliometrix in R, complemented by content analysis of 125 selected papers. The findings indicate that case studies, Life Cycle Assessment (LCA), and statistical analyses are popular methods in CASC research. Optimization models play a crucial role in decision-making processes, yet their application remains largely traditional, lacking with real-world validation and interdisciplinary approaches, and with limited integration of emerging technologies such as Artificial Intelligence (AI) and Machine Learning (ML), which could enhance predictive capabilities and system adaptability. Despite increasing research on the economic and environmental dimensions of CASC, the findings highlight that the social dimension remains underexplored. Future research should focus on bridging this gap by examining the roles and interconnections of diverse stakeholders and developing frameworks to evaluate the social impact of CASC initiatives. To support the transition, policymakers should implement targeted subsidies and regulatory frameworks that incentivize circular practices and ensure their equitable adoption. Businesses in the agri-food sector should embrace innovative waste valorization strategies and strengthen collaborations with local producers to enhance sustainability and resilience in supply chains. By integrating these approaches, CASC can be effectively implemented, bridging the gap between theoretical research and real-world applications, ultimately fostering a sustainable, resilient, and socially inclusive agri-food system.